2016
DOI: 10.1186/s12889-016-3895-y
|View full text |Cite
|
Sign up to set email alerts
|

Type of sexual intercourse experience and suicidal ideation, plans, and attempts among youths: a cross-sectional study in South Korea

Abstract: BackgroundDespite abundant theoretical evidence of higher rates of suicide among lesbian, gay, and bisexual (LGB) youths, little is known about the relationship between suicide and types of sexual intercourse experience in youths. This study examines the association between the type of intercourse experience and suicide risk outcomes (SROs: suicidal ideation, plans for suicide, suicidal attempts) from the Korea Youth Risk Behavior Web-based Survey.MethodsWe analyzed cross-sectional data from 146,621 students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The Korea Youth Risk Behavior Web-based Survey is the only national-level health survey in Korea measuring sexual orientation by asking respondents to indicate the gender of the person with whom they had a sexual intercourse. These data enabled studies to compare the health status of LGB adolescents with heterosexual counterparts [ 13 - 15 ]. To facilitate LGBT health studies in Korea, sexual orientation needs to be included as a demographic variable in national-level health surveys, such as the KNHANES and Work Environment Survey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Korea Youth Risk Behavior Web-based Survey is the only national-level health survey in Korea measuring sexual orientation by asking respondents to indicate the gender of the person with whom they had a sexual intercourse. These data enabled studies to compare the health status of LGB adolescents with heterosexual counterparts [ 13 - 15 ]. To facilitate LGBT health studies in Korea, sexual orientation needs to be included as a demographic variable in national-level health surveys, such as the KNHANES and Work Environment Survey.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the paucity of existing studies in the field, previous literatures regarding health disparities of LGB population in Korea have the following limitations. First, most studies were on the health disparities of LGB adolescents, using the Korea Youth Risk Behavior Web-based Survey which is the only nationally representative data that includes sexual orientation in the questionnaire [ 13 - 15 ]. On the other hand, because of the absence of sexual orientation measure in national health surveys targeting adults, there are only few studies on health disparities of adult sexual minorities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A study in China noted that male adolescents who reported same-sex romantic attraction or both-sex romantic attraction were more likely to report past-year suicidal ideation and suicide attempts than their counterparts who identified as heterosexual. 7 Another study in South Korea found that male youths who reported experiences of same-sex or both-sex sexual intercourse were more likely to report a history of suicidal ideation, suicide planning, and suicide attempts compared with those with opposite-sex sexual intercourse experiences only, 8 suggesting that greater risk of suicide for sexual minority youths is not specific to Western developed societies.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of a national cross-sectional survey in Chinese adolescents found that victimization of bullying mediated the associations of sexual minority status with suicidality [28] and poor sleep quality [29]. Analysis of the Korea Youth Risk Behavior Web-based Survey found that same- and both-sexes intercourse related suicidality is strongly linked to victimization of bullying among youths [30]. Therefore, factors associated with sexuality-related victimization of bullying during childhood and adolescence in Asian countries warrant further investigation to offer a basis for developing prevention and intervention programs aimed at reducing bullying of sexual minority youths.…”
Section: Introductionmentioning
confidence: 99%